Предмет: Математика,
автор: Цветочек134
ПОМОГИТЕ ПОЖАЛУЙСТА И ОБЪЯСНИТЕ,как делать?
Приложения:
Ответы
Автор ответа:
0
приводим к общему знаменателю
(х-4)/6 - (6х+3)/6 =3
(х-4-6х-3)/6 =3
-5х-7=6×3
-5х = 18+7
х=-25/5
х=-5
(х-4)/6 - (6х+3)/6 =3
(х-4-6х-3)/6 =3
-5х-7=6×3
-5х = 18+7
х=-25/5
х=-5
Похожие вопросы
Предмет: Обществознание,
автор: sarangerelganzorig
Предмет: Русский язык,
автор: Gulamovasevgina
Предмет: Русский язык,
автор: snezanamihajlova949
Предмет: Математика,
автор: msk96
Предмет: Биология,
автор: nurik9630